The Role of Media in Enhancing Communicative Competence of the Learners at Tertiary Level – An Analytical Study - Abilasha, R.; Ilankumaran, M. (International Journal of Engineering and Technology, 2018)
Media is a channel through which every message is communicated using a language in a meaningful way. The language used in media can be said to be â€˜specificâ€™ and there arises a need to have the course – Mass Communication Programme. Communicative competence means the capability to employ language effectively and aptly in social contexts and circumstances. Testing communicative competence is a challenging format by which the teachers assess the competence of learners. This includes information gap and role-play activities for speaking, letter writing, note-taking and summarising. The combination of all these enhance listening and writing competencies. An investigation has been conducted among the students to develop the communicative competence through media such as newspapers, internet, T.V, Radio etc. 50 respondents from two colleges, located in rural and urban areas, with 25 students each from a college, have been chosen for analysis. A questionnaire is used as a tool for the purpose of analysing communicative competence of the selected second year students of arts and science courses. This paper focuses on the importance of media in developing the language skills among the students at tertiary level.Â Â Â